ANALISIS KOMPARATIF PENDAPATAN USAHATANI KUBIS (Brassica oleracea) DI KELURAHAN AGUNG LAWANGAN KOTA PAGAR ALAM DAN DESA TANJUNG KARI KABUPATEN OKU SELATAN PROVINSI SUMATERA SELATAN - Endang Lastinawati, Varenra Rendy Wiranata, Henny Rosmawati, (Program Studi Agribisnis Fakultas Pertanian Universitas Baturaja, 2024)
Cabbage (Brassica oleracea) is one of the horticultural crops that is widely needed and consumed by the Indonesian people. Although the demand for cabbage is relatively high, farmers still face differences in income from their cabbage farming businesses. This study aims to compare the income of cabbage farming businesses in Pagar Alam City and South OKU Regency. This study was conducted in Agung Lawangan Village, Dempo Utara District, Pagar Alam City; Tanjung Kari Village, Pulau Beringin District; and South OKU Regency. The selection of the research location was carried out deliberately because Pagar Alam City and South OKU Regency are cabbage producers in South Sumatra. The research method used in this study is the survey method. The sampling method used is the disproportioned cluster random sampling method, which takes a sample of 30 people from each farmer population at the research location. The objectives of this study were answered using the income formula, which was then tested statistically through the independent sample mean difference test. The results showed that the income of cabbage farming businesses in Agung Lawangan Village, Pagar Alam City, was higher than the income of cabbage farming businesses in Tanjung Kari Village, South OKU Regency.